1984
DOI: 10.1021/i300013a006
|View full text |Cite
|
Sign up to set email alerts
|

The development of carborane-siloxane polymers

Abstract: The discovery of carborane-siloxane polymers in the early 1960's furnished a promising lead in the search for hlgh-temperature performance properties. However, the pioneering processes for carborane and carborane-siloxane synthesis Involved difficult procedures and/or low efficiencies. This severely limited not only the large-scale preparation of carboranes and linear carborane-siloxane polymers but also effectively eliminated the preparation of carboranes in the research laboratory. Thus a need existed for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…7,8 For example, carborane containing polysiloxanes have been demonstrated to show dramatically improved thermal and chemical stability over the parent polymers. 9 In the area of conjugated, electroactive polymers it has been shown that the incorporation of carborane as a side-chain unit in polyuorenes can increase the glass transition temperature and suppress aggregation in the solid state. 1 Carboranes exist in three isomers, differentiated by the relative position of carbon atoms in the cage structure.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 For example, carborane containing polysiloxanes have been demonstrated to show dramatically improved thermal and chemical stability over the parent polymers. 9 In the area of conjugated, electroactive polymers it has been shown that the incorporation of carborane as a side-chain unit in polyuorenes can increase the glass transition temperature and suppress aggregation in the solid state. 1 Carboranes exist in three isomers, differentiated by the relative position of carbon atoms in the cage structure.…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods is based on the synthesis of silanol derivatives of carboranes 1,7-[(HO)Me 2 Si] 2 C 2 B 10 H 10 which react further with compounds of a general formula SiR 2 L 2 , where R = amino, carbamate or ureido groups and L = NMe 2 or an amide group (Scheme 1) [45][46][47][48]. Thus, the reaction of bis(ureido)silanes results in linear polymers with the molecular masses over 250000.…”
Section: Polydimethylsiloxanes With Carboranyl Substituentsmentioning
confidence: 99%
“…Yet another method is based on the reaction of dilithium derivatives of carboranes with diorganosiloxanes bearing terminal ≡Si-Cl groups [47]. A limitation of this method is side reactions that are accompanied by the cleavage of siloxane bonds.…”
Section: Polydimethylsiloxanes With Carboranyl Substituentsmentioning
confidence: 99%
“…Besides, the large volume of three‐dimensional cage endows carboranes with strong shielding effect on adjacent segments. Therefore, carboranes were incorporated into many traditional polymers to improve their thermal stability including polysiloxanes, epoxy resins, phenolic resins, aromatic polymers, etc. With the increasing appearance of new polymers, carboranes expanded their application fields such as dendrimers and conjugated polymers with light‐emission property …”
Section: Introductionmentioning
confidence: 99%